Intracellular Signaling in Key Pathways Is Induced by Treatment with Ultrasound and Microbubbles in a Leukemia Cell Line, but Not in Healthy Peripheral Blood Mononuclear Cells - Ragnhild Haugse; Anika Langer; Stein-Erik Gullaksen; Silje Maria Sundøy; Bjørn Tore Gjertsen; Spiros Kotopoulis; Emmet McCormack (MDPI AG, 2019)
Treatment with ultrasound and microbubbles (sonoporation) to enhance therapeutic efficacy in cancer therapy is rapidly expanding, but there is still very little consensus as to why it works. Despite the original assumption that pore formation in the cell membrane is responsible for increased uptake of drugs, the molecular mechanisms behind this phenomenon are largely unknown. We treated cancer cells (MOLM-13) and healthy peripheral blood mononuclear cells (PBMCs) with ultrasound at three acoustic intensities (74, 501, 2079 mW/cm2) ± microbubbles. We subsequently monitored the intracellular response of a number of key signaling pathways using flow cytometry or western blotting 5 min, 30 min and 2 h post-treatment. This was complemented by studies on uptake of a cell impermeable dye (calcein) and investigations of cell viability (cell count, Hoechst staining and colony forming assay). Ultrasound + microbubbles resulted in both early changes (p38 (Arcsinh ratio at high ultrasound + microbubbles: +0.5), ERK1/2 (+0.7), CREB (+1.3), STAT3 (+0.7) and AKT (+0.5)) and late changes (ribosomal protein S6 (Arcsinh ratio at low ultrasound: +0.6) and eIF2α in protein phosphorylation). Observed changes in protein phosphorylation corresponded to changes in sonoporation efficiency and in viability, predominantly in cancer cells. Sonoporation induced protein phosphorylation in healthy cells was pronounced (p38 (+0.03), ERK1/2 (−0.03), CREB (+0.0), STAT3 (−0.1) and AKT (+0.04) and S6 (+0.2)). This supports the hypothesis that sonoporation may enhance therapeutic efficacy of cancer treatment, without causing damage to healthy cells.